Effect of dibutyl phthalate on microbial function diversity and enzyme activity in wheat rhizosphere and non-rhizosphere soils. (October 2020) - Gao, Minling; Dong, Youming; Zhang, Ze; Song, Zhengguo
Abstract: The pollution of farm soils by the plasticizer dibutyl phthalate (DBP) should be researched owing to the extensive use of plastic film. We investigated the influence of DBP on microbial communities and enzyme activities in rhizosphere and non-rhizosphere soil during the different growth stages of wheat and determined the response through simulations. The results indicated that protease, polyphenol oxidase, and β-glucosidase activity in soil decreased with increasing DBP dosage, while dehydrogenase, urease, and acid phosphatase activities increased. Moreover, the effects of DBP on soil enzyme activity gradually weakened with DBP degradation. Dibutyl phthalate has a certain inhibitory effect on the activity, diversity, and heterogeneity of microorganisms in soil. In addition, DBP can increase the utilization of amines and carboxylic acids and decrease the utilization of carbohydrates and amino acids by soil microorganisms. According to the Gaussian and molecular docking analysis, we considered that monobutyl phthalate and DBP could affect the utilization of amino acids by Proteobacteria . The enzyme activity, microbial activity, and heterogeneity of rhizosphere soil were higher than those of non-rhizosphere soil. Microbial carbon source utilization in rhizosphere and non-rhizosphere soils depends on wheat growth, soil type, and DBP dosage. Owing to the widespread presence of DBP in agriculture, negative effects of phthalic acid esters should be considered in relation to soil quality and food safety in future. Graphical abstract: Image 1 Highlights: The effect of DBP on soil enzyme activity would gradually weaken with wheat growth. Monobutyl phthalate could interact with amino acids through hydrogen bonding. The utilization of amino acids by microorganisms was decreased. The enzyme and microbial activity were higher in rhizosphere soil.